Work zone sign design for increased driver compliance and worker safety. (September 2017) - Rahman, Md Mahmudur; Strawderman, Lesley; Garrison, Teena; Eakin, Deborah; Williams, Carrick C.
Highlights: The impact of sign content, frame refresh rate, and sign placement on driver behavior was examined. Results found significant effect of refresh rate on driver behavior. Longer fixation duration on DMS was observed when worker presence was mentioned. Abstract: Many studies have investigated the effect of dynamic message signs (DMS) on drivers' speed reduction and compliance in work zones, yet only a few studies have examined the design of sign content of DMS. The purpose of this study was to develop design standards for DMS to improve driver compliance and worker safety. This study investigated the impact of sign content, frame refresh rate, and sign placement on driver speed reduction, compliance, and eye movements. A total of 44 participants were recruited for this study. Each participant completed 12 simulated driving tasks in a high-fidelity driving simulator. A small-scale field study was also conducted to test the effect of DMS on vehicle speed in a highway work zone. Results showed sign content and placement had no impact on speed reduction and compliance. However, sign frame refresh rate was found to have a significant effect on drivers' initial speed and speed reduction. Participants had longer fixation duration on DMS when worker presence was mentioned in the sign content. Results of the field study suggested that the DMS is most effective at night.